EXPO: Self-Development Training Program to Introduce Emotional Competence for First-Year Psychology Students - Wedyaswari, Miryam; Syamila, Millati; Widowati, Devita Ratna (Asia Pacific Higher Education Research Journal (APHERJ), 2020)
Emotional competence is an influencing factor for an academic adjustment. Therefore, an orientation program facilitating those competency is needed for first-year students. The training was designed to help them understand emotional competence. This study examined whether the EXPO: Self Development Training Progam could improve knowledge about emotional competence. This study used pre-experimental design. Participants were all first-year students in psychology major (n=155; M=31; F=124), while emotional competence was assessed by using Goleman’s Emotional Competence Inventory (R=.879). The Wilcoxon signedrank test was used to analyze before and after programs’ data. There was a statistically significant knowledge improvement in the students’ emotional competence following the EXPO program (z=?4.068, p<.05), with a medium effect size (r=.33) with the highest improvement found in empathy (z=9.248, p<.05, r=.75). The emotional competence intervention efficacy study should be offered to use a Randomized Controlled Trial (RCT) design to generalize the overall effectiveness of the intervention program.